THE INFLUENCE OF ONLINE PRESENCE ON THE INTENSITY OF EMPLOYEE DISCIPLINE AT PT. PEGADAIAN (PERSERO) DAYA MAKASSAR BRANCH - Anisa Apriliani Malik; Sri Andayaningsih; A.Muhiddin Daweng (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the effect of Online Presence on Employee Discipline Intensity at PT. Pegadaian (Persero) Daya Makassar Branch. The population in this study were all employees of PT. Pegadaian (Persero) Daya Makassar Branch has 35 employees. The type of research is descriptive quantitative. The data sources used are primary data sources, namely information originating from observations and questionnaires. Meanwhile, secondary data sources are data sources obtained from documentation or literature study. The data analysis technique used is simple linear regression analysis using statistical calculations by Statistical Package for the Social Science (SPSS) version 24 application.The results of the research show that Online Presence (X) has a positive and significant effect on employee discipline intensity (Y) seen from the results of the calculated t value > t table (4,163 > 1.690) and the significant value 0.00 ˂ 0.05